BAGAIMANA KEPRIBADIAN DAN PEMBERDAYAAN PSIKOLOGIS MENINGKATKAN PERILAKU PROAKTIF KARYAWAN START-UP? - Saifullah, Mokhamad Arif; Tarigan, Medianta; Nurendah, Gemala (JURNAL PSIKOLOGI INSIGHT, 2019)
This research aimed to know the effect of personality traits and psychological empowerment on proactive behavior of start-up company employees. The research used quantitative method with 350 participants. The instruments were Big Five Inventory (BFI), Psychological Empowerment Scale (PES), and Proactive Work Behavior Scale (PWBS). With multiple regression we predict effect of personality traits and psychological empowerment on proactive behavior. The results were there were significant effects of personality traits and psychological empowerment on proactive behavior of start-up company employees.